2020
DOI: 10.1111/ppc.12606
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Stress Scale (NSS): Reliability and validity of the Turkish version

Abstract: This study aims to conduct the reliability and validity study of the Turkish version of the Nurse Stress Scale (NSS), which determines the job stress of nurses. Design and Methods:The sample of the methodological study consisted of 349 nurses. Results:The factor load of the scale was in the appropriate range (0.32-0.79), Cronbach's α was determined as .928, and the item total score correlations ranged between 0.418 and 0.662. The test-retest reliability coefficient was determined to be r = .859.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(35 reference statements)
0
7
0
1
Order By: Relevance
“…Cronbach α scores for the subscales ranging between .67 to .89 have been reported across multiple countries and practice settings (Newman et al, 2020 ). Other researchers only reported the overall scores (Alenezi et al, 2018 ) or completed principal component analysis to support the use of only the total NSS score (Mert et al, 2021 ). Pathak et al ( 2013 ) suggested that factor analysis completed with the involved study sample is required to better address the differences in working conditions in LMICs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cronbach α scores for the subscales ranging between .67 to .89 have been reported across multiple countries and practice settings (Newman et al, 2020 ). Other researchers only reported the overall scores (Alenezi et al, 2018 ) or completed principal component analysis to support the use of only the total NSS score (Mert et al, 2021 ). Pathak et al ( 2013 ) suggested that factor analysis completed with the involved study sample is required to better address the differences in working conditions in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…Pathak et al ( 2013 ) suggested that factor analysis completed with the involved study sample is required to better address the differences in working conditions in LMICs. In a study with 349 nurses in Turkish and after modifying the items loading on each subscale and rewording some of the subscales, the reliability coefficients for the subscales ranged from .63 to .81 (Mert et al, 2021 ). Other researchers have modified the original NSS (Alkrisat & Alatrash, 2017 ) to better reflect hospital-based practice, to better reflect specific national context (Kim et al, 2015 ), or for emergency room practice (Yuwanich et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NSS, developed by Gray-Toft and Anderson, consists of 34 items and seven factors including “Uncertainty Concerning Treatment,” “Workload,” “The Death of a Patient,” “Conflict with a Physician,” “Conflict with Peers,” “Insufficient Support,” and “Suffering Patient.” 27 The scale was translated and validated in Turkish by Mert et al 28 in 2020. The items rated using the 4-point Likert system as (1) never, (2)sometimes, (3) often, (4) very often.…”
Section: Methodsmentioning
confidence: 99%
“…The Korean Occupational Stress Scale (KOSS) was developed in Korea; it consists of eight subscales of job stressors: physical environment, job demand, insufficient job control, interpersonal conflict, job insecurity, organizational system, lack of reward, and occupational climate [12]. Multidimensional scales to measure PF at work in specific industries were also developed and reported such as for construction workers [13], teachers [14], nurses [15], and dentists [16].…”
Section: Introduction 1background and Previous Workmentioning
confidence: 99%